Information Complexity and Behavior Intention to Prescribe Antibiotics Based on the Antimicrobial Susceptibility Testing Report: The Mediating Roles of Information Overload and Attitude - Wang, Ying; Zhang, Xinping; Zhou, Qian; Xu, Xiaojun; Liu, Xiaofeng; Lu, Shaohui (Frontiers in Pharmacology, 2021)
Background: The antimicrobial susceptibility testing (AST) report has guiding significance for physicians to prescribe antibiotics. This study aims to examine the effect of the AST report information complexity on physician's intention to prescribe antibiotics based on the AST report, as well as the mediating role of information overload and attitude. Methods: A cross-sectional study conducted on 411 physicians in a general hospital in China in July 2021. Data were collected by a self-reported questionnaire. A serial multiple mediation model was tested to explore the sequential causality between the information complexity of the AST report, information overload, attitude, and behavior intention to prescribe antibiotics based on the AST report by using the SPSS macro PROCESS program. Results: Information complexity, information overload, attitude and behavior intention were significantly correlated (p<0.01). Information complexity can not only have a direct positive impact on the intention to prescribe antibiotics based on the AST report (effect=0.173; SE=0.044; Boot95%CI: LL=0.089, UL=0.260), but also have an indirect impact on behavior intention through the independent mediating role of information overload (effect=0.025; SE=0.011; Boot 95%CI: LL=0.008, UL=0.050) and the independent mediating role of attitude (effect=0.130; SE=0.025; Boot 95%CI: LL=0.086, UL=0.180), while the chain of information overload and attitude played a masking effect between information complexity and behavior intention (effect=-0.013; SE=0.004; Boot 95%CI: LL=-0.023, UL=-0.005). Conclusion: The increase in information complexity can encourage physicians to prescribe antibiotics based on the AST report, information overload and attitude can promote this effect. It is necessary to provide physicians with sufficient information to prescribe antibiotics without increasing the burden on them. At the same time, publicity and standardized training should be conducted for physicians to interpret the AST report better and faster.